Evaluation of raw sunflower seed (RSFS) in broiler diets - OLUGBEMI, T S; ADUKU, A O; OGUNDIPE, S O; ADEYINKA, I A (The Indian Journal of Animal Sciences, 2014)
The performance ofbroilers fed raw sunflower sted (RSFS) diets was evaluated. In a feeding trial, 216 were randomly assigned to 6 isonitogenous and isocaloric diets containing 0, 20, 20, 30, 40 and 50% RSFS. A completely randomized design comprising. 6 treatments, 3 replicates/ treatment and 12 birds/replicate was used. The effect of the treatment on feed intake, weight gain and feed conversion efficiency was recorded on weekly basis. The effect of treatments on carcass characteristics was measured at the end of the 8 weeks feeding trial. Results of the trial showed that 20% RSFS was optimum during the starter phase (0- 4 weeks) for the weight gain, feed conversion efficiency and weight at fourth week. Only at the 50% inclusion level there was a significant (P< 0.05) difference In feed intake. The highest monality was recorded in the 40% SFS group. Nonsignificant (P>0.05) differences existed in the feed cost/kg weight gain. During the finisher phase (5 - 8 weeks), there were no significant differences (P>0.05) between the 0, 10, 20 and 40% SFS groups for weight gain, feedintake and feed conversion efficiency. Feed cost/kg weight gain differed significantly beyond 30% SFS inclusion. The weight at 8 weeks of the 0 to 20% SFS groups were similar. Nonsignificant (P>0.05) results were observed with respect to liver, heart, gizzard, abdominal fat, head, leg, blood, feather, lung and spleen percentages, gut length, caecum length and dressing percentage. Significant differences existed across treatments for gizzard percentages.